The conformational heterogeneity of proteins. - Hutnik, Cindy Mary-Lynn. (University of Ottawa (Canada), 1990)
Time-correlated single photon counting and steady-state fluorescence spectroscopy were used to investigate the conformational properties of select proteins. Specifically, the role of naturally associated metal ions in modulating the conformation of members from two families of metalloproteins was examined. Two homologous bacterial copper-containing azurins were purified from Pseudomonas fluorescens (ATCC 13525) and Pseudomonas aeruginosa (ATCC 10145). The intrinsic fluorescence of the native Cu(II) single tryptophan-containing protein, as well as experimentally prepared Cu(I), Ni(II), Co(II) and metal-free derivatives demonstrated that the metal centre of these redox proteins played an important role in the conformational heterogeneity of the protein. Such an effect was strongly dependent on the nature of the metal ion. From the calcium-binding superfamily, the single-tryptophan containing isotype III component of parvalbumin was purified from codfish. The previous notion that this protein was a Ca(II)/Mg(II)-specific protein was shown to be due to an experimental artefact arising from the use of the soluble chelator EGTA. The Ca(II)-specific conformational changes of cod III parvalbumin were compared with those of the highly homologous Ca(II)-binding tumour protein oncomodulin. Since native tumour oncomodulin was devoid of tryptophan, a site-specific mutant of oncomodulin with tryptophan in the identical position of the parvalbumin tryptophan was examined. The results showed that the ability of oncomodulin to function as a modulator (unlike parvalbumin) may be due to relatively subtle Ca(II)-specific conformational changes. Details of these changes were obtained by an examination of a number of oncomodulin mutant proteins in which the non-fluorescent phenylalanine, and the highly fluorescent tryptophan had been substituted into various positions of the two Ca(II)-binding loops. The results demonstrated that the binding of the first equivalent of Ca(II) induced greater than 90% of the conformational changes experienced by various probed positions, but that the second equivalent of Ca(II) played an important role in orienting the two Ca(II)-binding loops relative to each other.
Keywords: Chemistry, Biochemistry.